Escola família agrícola de Serra do Mel (EFAMEL): produção de identidades e construção dos sujeitos - Duarte, Maria Rosivania Pereira Feitosa (Universidade Federal Rural do Semi-Árido, 2019)
This research aims to make a historical survey of the extinct Serra do Mel Agricultural Family School (EFAMEL), aiming to analyze if there were contributions left by this institution to the construction of the identity of the subjects who studied there, with specific objectives: ) to analyze the process of foundation, deployment, organization and operation of EFAMEL; b) discussing their pedagogical practices; c) investigate the relationship of the School with the production of the peasant identity of the former students. The relevance of this work is justified by the importance of this School for the municipality of Serra do Mel-RN, during its operation for a little more than a decade (1990-2002). The methodological paths started with bibliographical research on the themes, where I took as a base Nosella (2012), Teixeira; Bernartt and Trindade (2008), Chaves and Fochiera (2014) to talk about EFAs; to discuss the Pedagogy of Alternation, I spoke to Cordeiro; Reis and Hage (2011); to think about the concept of Identity, I rely on Hall (2005), Maheirie (2002), Oliveira (2003) and Vieira (2006); to discuss about the production of memories, Albuquerque Jr. (1994), Bosi (1994) and Guimarães Neto (2005); on the methodology of research, I found myself in Minayo (2002), Gil (2008) and Boni and Quarema (2005). Semistructured interviews were then conducted with former students, former teachers and the founder of this school. After the interviews, they were transcribed and thematized. The analysis allowed us to conclude that this school had an influence on the formation of the identity of the subjects that were part of this educational experience, enhancing their relationship with the field and influencing their professional and daily practices
Monografia
Keywords: EFAs; Pedagogia da alternância; Identidade; Educação do campo; Serra do Mel; EFAs; Pedagogy alternation; Identity; Field education; Serra do Mel; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL